Examining the mechanism of action of small-molecule negative allosteric modulators of the human chemokine receptor CXCR2 - Nesheva, Desislava (2022)
The CXC chemokine receptor 2 (CXCR2) is a G protein-coupled receptor (GPCR) with key functions in neutrophil trafficking and activation both during normal homeostasis, and in acute and chronic inflammation. In addition, CXCR2 signalling promotes tumour survival through the mediation of cell proliferation and metastasis, angiogenesis and immune suppression. Despite the therapeutic potential of inhibiting CXCR2 for the treatment of inflammatory conditions and cancer, there is currently not an approved treatment at the receptor. This is largely due to the challenging task of balancing the successful treatment of inflammation or cancer suppression whilst maintaining the homeostatic function of the immune system intact when blocking CXCR2 (Cheng et al., 2019a).